Cloning of deoxyribonucleic acid regions encoding a heat-labile and heat-stable enterotoxin originating from an enterotoxigenic Escherichia coli strain of human origin. - Yamamoto, T (1980)
A heat-labile and heat-stable enterotoxin (LT+ ST+) plasmic (62.7 kilobases in size) was isolated from an enterotoxigenic Escherichia coli human strain, H10407, and used for analysis of the LT+ and ST+ deoxyribonucleic acid (DNA) regions. A DNA segment containing the LT+ and ST+ DNA regions, which consisted of two restriction endonuclease EcoRI fragments (E1 and E2), was inserted into the cloning vehicle ColE1::Tn5 by EcoRI digestion and subsequent ligation. Further cloning experiments localized the LT+ DNA region on a 5.1-kilobase restriction endonuclease PstI fragment present over the junction between the E1 and E2 fragments, as seen in the original LT+ ST+ plasmid, and the ST+ DNA region on a 1.5-kilobase PstI fragment present in either the E1 or E2 fragment. A change in the relative orientation of the E1 and E2 fragments resulted in altered levels of LT production. The relative orientation of the ColE1::Tn5 fragment to the E1 and E2 fragments also markedly influenced both LT and ST production levels. The LT+ ST+ E1-E2 region contained two unique DNA sequences consisting of a DNA segment flanked by inverted repeats which were readily distinguished from each other by size. The cloned ST+ PstI fragment was structurally very similar to one of these unique DNA sequences present in the LT+ ST+ E1-E2 region.